2014
DOI: 10.9790/1959-03151721
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a “Planned Teaching Programme”(PTP) on Knowledge Related to Reproductive Tract Infections Among Rural Women

Abstract: The most important period in the life span of women is the reproductive period, which extends from menarche to menopause. Reproductive tract infections are endemic in developing countries and entail a heavy toll on women. If untreated reproductive tract infections can lead to adverse health outcomes such as infertility, ectopic pregnancy and increased vulnerability to transmission of HIV. Quantitative evaluative approach was used and research design was one group pre-test post-test design. Sample were women of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
3
3
0
Order By: Relevance
“…This can be attributed to lack of awareness in rural areas as compared with the urban areas. These findings are in agreement with the findings of Chauhan et al, 32 who concluded that there was a highly statistically significant relation between students' total knowledge score level and their age, education and marital status. Hence, it is interpreted that there is an association between demographic variables with pretest knowledge score and the impact of program on the level of knowledge of students.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This can be attributed to lack of awareness in rural areas as compared with the urban areas. These findings are in agreement with the findings of Chauhan et al, 32 who concluded that there was a highly statistically significant relation between students' total knowledge score level and their age, education and marital status. Hence, it is interpreted that there is an association between demographic variables with pretest knowledge score and the impact of program on the level of knowledge of students.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the finding of the current study is supported by Alka et al, 22 who studied "Effectiveness of a "planned teaching programme" (ptp) on knowledge related to reproductive tract infections among rural women", They found that, the mean of posttest knowledge score (16.93±3.70) was higher compared with the mean of pretest knowledge score (13.25±3.71). There was a significant difference between the mean pretest and post-test scores at P<0.05 levels.…”
Section: Discussionsupporting
confidence: 78%
“…Entisar et al (2017) In addition who stated that the mean score of knowledge of the studied sample as regards the anatomy of the female reproductive system, natural defense mechanism in the female genital system, and characteristics of normal vaginal discharge were significantly improved after implementation of educational program. Moreover Chauhan et al (2014) who studied the effectiveness of planned teaching program about knowledge related to reproductive tract infections (RTIs ( among rural women. Reported that there were a significant difference between the mean pre and post-test knowledge related to anatomy, physiology of reproductive tract, and types of genital tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study conducted in Udupi, the mean knowledge score of the SHG women had improved from 12.88 to 26.88, and the program was found to be effective (p<0.01) (Lobo, 2013). There was a signi icant improvement in the knowledge scores of the women after the teaching program in Uttarakhand (13.25 to 16.93) (Chauhan et al, 2014).…”
Section: Resultsmentioning
confidence: 94%
“…With 5% level of signi icance, 80% power, a clinically signi icant difference(d) of 3 and variance (σ) =3.71 (Chauhan et al, 2014); the minimum estimated sample size in each group was 23.98. Expecting 20% sample attrition the sample size was adjusted to 29.…”
Section: Sample Sizementioning
confidence: 99%